Level I/II autonomy in robotically navigated lithotripsy: comprehensive system evaluation and performance assessment. - Athanasiou, Lambros; Senthil Kumar, Manivannan; King, Franklin; Wollin, Daniel A.; Hata, Nobuhiko (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: Laser lithotripsy is a minimally invasive procedure performed by a urologist using a ureteroscope, a device composed of a flexible laser fiber and a camera. The camera is used to physically view and manually target the stone ablated by the laser. The procedure involves the risk of unintentional trauma caused by the laser when the stones are out of target due to their retro-pulsive movement. Methods: To minimize clinical complications, we propose a Level I/II autonomous system in robotic lithotripsy. The system consists of a robotic catheter and an integrated U-Net segmentation method. The system aims to automatically target the stones during lithotripsy and guide ureteroscope navigation autonomously. Results: The proposed system is designed and validated using a phantom specifically manufactured to investigate the feasibility of autonomous stone ablation. An overall target accuracy of 99.97% (leave-one-out: 99.971 min, 99.975 max) was reported. Conclusions: We successfully implemented a stone targeting method and integrated it with our robotic system to evaluate the level of success in autonomously targeting the stones. The results, indicate that autonomy in robot assisted lithotripsy is feasible.